AVALIAÇÃO DO POTENCIAL DE RISCO NA BIOACUMULAÇÃO DE METAIS EM Hoplias aimara NO ALTO RIO ARAGUARI- BACIA AMAZÔNICA- BRASIL - VIANA, Lucilene Finoto; CARDOSO, Claudia Andrea Lima; FLORENTINO, Alexandro Cezar (ANAIS DO ENIC, 2020)
-